2020
DOI: 10.1136/jitc-2020-001687
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant or delayed anti-TNF differentially impact on immune-related adverse events and antitumor efficacy after anti-CD40 therapy

Abstract: BackgroundConcomitant tumor necrosis factor (TNF) neutralization in combination with immune checkpoint inhibitors (ICIs) reduces clinical immune-related adverse events (irAEs) and appears to improve antitumor efficacy in preclinical tumor models. Agonistic antibodies targeting costimulatory receptors such as CD40 represent an additional strategy to boost antitumor immune response and potentiate the activity of ICIs. However, the dose-limiting toxicities observed in anti-CD40-treated cancer patients have hinder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…TNF inhibitors are used in the clinical management of toxicities associated with the use of anti–CTLA-4 antibodies ( 25 , 40 ). In mouse models, they have been shown to ameliorate age-associated hyperinflammatory cytokine responses produced by systemic immune activation of macrophages ( 42 ) as well as immune-related adverse events produced by anti-CD40 in the absence of chemotherapy ( 43 ). In our studies, we observed TNF-dependent hepatotoxicity triggered by CD40 chemoimmunotherapy even in young mice and independent of macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…TNF inhibitors are used in the clinical management of toxicities associated with the use of anti–CTLA-4 antibodies ( 25 , 40 ). In mouse models, they have been shown to ameliorate age-associated hyperinflammatory cytokine responses produced by systemic immune activation of macrophages ( 42 ) as well as immune-related adverse events produced by anti-CD40 in the absence of chemotherapy ( 43 ). In our studies, we observed TNF-dependent hepatotoxicity triggered by CD40 chemoimmunotherapy even in young mice and independent of macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Results showed that although the antitumor effect on breast and colon cancer models of anti-CD40 decreased, the most suitable combination was simultaneous rather than delayed treatment with anti-TNFα administration. In this way, irAEs were prevented [ 250 ]. In the clinical setting, a recent report on patients from the Dutch Melanoma Treatment Registry showed that those treated with ipilimumab and anti-PD1 with severe irAEs had longer survival.…”
Section: Immunotherapy Overviewmentioning
confidence: 99%
“…Depleting macrophages or neutrophils or blocking TNFa production was sufficient to prevent anti-CD40 induced liver damage, which is consistent with previous reports. 41,[53][54][55][56] Our study adds to these previous reports by demonstrating that the gut microbiota is critically required for anti-CD40-induced pathogenic immune cell infiltration/activation in the liver and for anti-CD40-induced cytokine release. While both macrophages and neutrophils were required for anti-CD40-induced liver damage, only macrophage depletion reduced anti-CD40-induced systemic TNFa release.…”
Section: Discussionmentioning
confidence: 75%